Rewritten Bible after fifty years: texts, terms, or techniques?: a last dialogue with Geza Vermes ; [papers of a Conference on the meanings and usages of the term rewritten Bible introduced by Geza Vermes in 1961 ; in Budapest on 10 - 13 july 2011] - Zsengellér, József; Vermès, Géza (Journal for the study of Judaism / Supplements, 2014)
"Rewritten Bible After Fifty Years presents the papers of a conference on the meanings and usages of the term Rewritten Bible introduced by Geza Vermes in 1961. Leading scholars of the topic discuss their new insights and ideas comparing with Vermes' initiative, whose participation on this conference was unfortunately the last chance for a life dialogue with him on this topic. Apart from the terminological discussions and comparisions several case studies widen the scope of the notion of Rewritten Bible/Scripture and rewriting as a genre and technique"--